Effects of perceived effectiveness in contract farming on adoption of best crop management practices among sugarcane farmers in Tanzania - Pato, Innocensia Dickson; Osewe, Maurice; Han, Jiqin (Frontiers in Sustainable Food Systems, 2024)
The resilience of agro-processing firms engaged in contract farming (CF) production heavily depends on the quality and quantity of supplies from their linked farmers. Adopting best crop management practices (BCMPs) is crucial to enhancing production and meeting the supply demands of contracting firms. Understanding the factors influencing farmers' decisions is key to successfully implementing strategies that promote BCMP adoption. This study explored the effects of farmers' perceptions of contract farming arrangement (CFA) effectiveness on sugarcane BCMP adoption, using survey data from 400 farmers in Tanzania. The results from both a multivariate probit model (for specific practices) and ordinal regression (for adoption intensity) revealed positive effects. In particular, the perceived effectiveness of pricing and payment systems and produce supply management had a stronger influence on BCMP adoption than resource support and extension service provision. These findings suggest that efforts to improve BCMP adoption among sugarcane contract farmers should not only focus on enhancing production capabilities through input, credit, and technical support packages but also emphasize the creation of robust incentive structures. Ensuring fair pricing, timely payments, and compliance with contract terms—alongside mechanisms to mitigate farmer loss risks—would significantly enhance BCMP adoption rates.